Faktor-Faktor Yang Memengaruhi Pertumbuhan Aktiva Produktif Bank Umum Syariah Pada 2017-2022 - hasibuan, salsabilah; Batubara, Sarmiana; Lestari, Sry (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2024)
Productive assets are investment assets that typically generate profit for their owners in each period. One of the crucial factors for banks in channeling funds that influence the growth of productive assets is inflation, NPF (Non-Performing Financing), and DPK (Third-Party Funds). Inflation is a continuous increase in prices over a certain period. NPF represents problematic financing in the form of less smooth financing, while DPK represents funds collected by banks from the public, both individuals, and businesses. Partially, inflation does not affect productive assets, with a t-statistic value of -1.758 t-table value of 1.667. Partially, NPF affects productive assets, with a t-statistic value of 2.340 t-table value of 1.667. Partially, DPK affects productive assets, with a t-statistic value of 2.007 t-table value of 1.667. Simultaneously, inflation, NPF, and DPK affect productive assets, with an F-statistic value of 3.321 and an F-table value of 3.13 (3.321 3.13). Therefore, it can be said that the growth of productive assets in Islamic banking has experienced unstable increases from year to year due to third-party funds. The research questions in the growth of productive assets in this study are whether inflation affects productive assets in BUS, whether NPF affects productive assets in BUS, whether DPK affects the growth of productive assets in BUS, and whether inflation, NPF, and DPK affect productive assets in BUS. The objective is to determine the extent to which the variables of inflation, Non-Performing Financing (NPF), and Third-Party Funds (DPK) influence the growth of productive assets in Islamic banking. The theory used in this research concerns the growth of productive assets, inflation, Non-Performing Financing (NPF), and Third-Party Funds (DPK) in relation to the growth of productive assets. The type of research employed is quantitative research, and the sampling technique used is purposive sampling with a sample size of 72. The source of data is secondary, and data collection techniques include literature study and documentation study through the official website www.ojk.co.id. Data processing was carried out using SPSS version 23. The results of partial data analysis indicate that the growth of productive assets is not influenced by inflation, with a t-statistic value of -1.758 and a t-table value of 1.667, so t-statistic (-1.758) t-table (1.667); NPF has a t-statistic value of 2.340 and a t-table value of 1.667, so t-statistic (2.340) t-table (1.667); DPK has a t-statistic value of 2.007 and a t-table value of 1.667, so t-statistic (2.007) t-table (1.667). Furthermore, the simultaneous research results (F-test) indicate that the F-statistic value is 3.321 and the F-table value is 3.13 (3.321 3.13), indicating an effect on all three variables. The determination coefficient results show that the R2 value is 0.128, meaning that inflation, NPF, and DPK can explain the productive assets variable by 12.8%, while the remaining 87.2% is explained by other variables outside the scope of this research.